2010
DOI: 10.4314/njps.v22i1-2.54857
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial effects of the aqueous extract of phyllantus amarus schumach and thonn against plasmodium Berghei in Swiss albino mice

Abstract: Summary:Phyllantus amarus Schumach and Thonn is a medicinal plant used commonly for the treatment of malaria-related symptoms by the general public in southeastern Nigeria. The present study determines the possible antiplasmodial effects of the aqueous extract of the leaves and stem of the plant against Plasmodium berghei infection using Swiss albino mice as models. The blood schizonticidal activity of the aqueous extract in early infection and in established Plasmodium berghei infection was assessed and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…In vitro the activity was lower at the concentration of 100, 50, 25 and 12.5 g/mL and compared with chloroquine (Traore et al, 2008). The aqueous extract of leaves and stem of P. amarus at doses of 108.33, 165 and 325 mg/kg in Swiss albino mice was found to cause a significant dose-dependent suppression of P. berghei parasites [p < 0.05] sulfadoxine/pyrimethamine caused a similar significant suppression of P. berghei parasites (Dapper et al, 2007). Ethanolic, methanolic and methylene chloride extracts of entire plant of P. amarus showed significant activity against the chloroquinesensitive strain of P. falciparum 3D7.…”
Section: Antiplasmodial Activitymentioning
confidence: 68%
“…In vitro the activity was lower at the concentration of 100, 50, 25 and 12.5 g/mL and compared with chloroquine (Traore et al, 2008). The aqueous extract of leaves and stem of P. amarus at doses of 108.33, 165 and 325 mg/kg in Swiss albino mice was found to cause a significant dose-dependent suppression of P. berghei parasites [p < 0.05] sulfadoxine/pyrimethamine caused a similar significant suppression of P. berghei parasites (Dapper et al, 2007). Ethanolic, methanolic and methylene chloride extracts of entire plant of P. amarus showed significant activity against the chloroquinesensitive strain of P. falciparum 3D7.…”
Section: Antiplasmodial Activitymentioning
confidence: 68%
“…However, results from in vivo studies by Ajala et al (2011) indicated that the aqueous extract of the whole plant of P. amarus was effective against P. falciparum and had a chemotherapeutic effect similar to that of chloroquine. According to Dapper et al (2007), P. amarus had significant antimalarial properties even though the effects were not sustained compared to effects of the combination of pyrimethamine and sulfadoxine. The differences in the level of anti-plasmodial activity exhibited by whole plant extracts might be due to the amount of the bioactive compounds extracted by the two different solvents.…”
Section: Resultsmentioning
confidence: 99%
“…They are: Cylicodiscus gabunensis (Okokon et al, 2006b), Uvaria chamae and Hippocratea africana (Okokon et al, 2006a), Enantia chlorantha and Cymbopogon giganteus (Agbaje and Onabanjo, 1991;Kimbi and Fagbenro-Beyioku, 1996), Cymbopogon citratus and Ocimum gratissimum (Tchoumbougnang et al, 2005), Cassia singueana (Adzu et al, 2003), Stachytarpheta cayennensis (Okokon et al, 2008), Striga hermonthica and Tapinanthus sessilifolius (Okpako and Ajaiyeoba, 2004), Tetrapleura tetraptera (Okokon et al, 2007b), Setaria megaphylla (Okokon et al, 2007c), Phyllanthus amarus (Dapper et al, 2007), Homalium letestui (Okokon et al, 2006c) and the plant formula 'Agbo-Iba' shown to protect mice against Plasmodium yoelii nigeriensis infection; the herbs used in this formula were decocted for 3 h and then administered to mice orally to evaluate the prophylactic and curative activities. Although the 'Agbo-Iba' formula was prophylactic and had no apparent significant side effects in mice, the formula had no curative activity against established infection (Nwabuisi, 2002).…”
Section: Scientific Authentication Of Antimalarial Activities Of Nigementioning
confidence: 99%